Exploring the Potential of Lactic Acid Fermentation for the Recovery of Exhausted Vanilla Beans - Hadj Saadoun, Jasmine; Levante, Alessia; Ferrillo, Antonio; Trapani, Francesca; Bernini, Valentina; Galaverna, Gianni; Neviani, Erasmo; Lazzi, Camilla (Frontiers in Nutrition, 2022)
The market value of vanilla is constantly growing, as it is the aroma most appreciated by consumers worldwide. The key component of the aroma of vanilla beans is vanillin, which can be directly extracted from the plant, produced by chemical synthesis, or by bioconversion of natural precursors. Due to the increasing consumers’ demand for products labeled as “natural”, extraction from vanilla pods results in a more valuable aroma source. Once the extraction is completed, what remains are the exhausted beans that still contain small seeds and other compounds, including varying amounts of vanillin trapped in the cellular structures of the plant. The application of fermentation of exhausted vanilla beans is proposed here as a strategy to recover “natural” vanillin and other valuable aroma compounds as a result of metabolic conversion by lactic acid bacteria (LAB). The aim of this study was to verify the fermentability of exhausted vanilla beans by-products for their valorisation, allowing the recovery of high-value molecules or new applications in food products. Design of Experiment (DoE) was used to screen a library of LAB strains to identify the best condition of fermentation in response to varying cultivation conditions. A comparison between mono and co-culture of LAB was assessed. Moreover, a sensory panel tests and the evaluation of the aromatic components by Solid Phase Micro Extraction-Gas Chromatography-Mass Spectrometry analysis were carried out to better understand the modification of the aroma profile after fermentation. Fermentation with LAB changed the volatile profile and sensory characteristics of the exhausted vanilla beans, and represents a promising method for valorization of these by-products.